(3GdUMjaI aj GdJLQHI GdUQjMIs - (3CHh TGcQ Hf jYbhH GdfUQGfj, aNQ GdOhdIs
(3ChdgG (B:s
(3bGd bO LQJ YGOI Gdbhe Cf jMedhG gPg GdUfGYI Ydi cd ZGQH hjHQhRgG ddeJYdejf ai cd bGdH hbO cfJ hbYJ Ydi eG QSeg GdTjN CHj YHO Gddg Hf Cejd ai bUjOJg GdeTghQI HQSGdI GdTeS Edi GdgdGd s
(3BNQgG (B:s
(3aUd HYO MeO Gddg ceG gh Cgdg abO Cedi CHh YHO Gddg eMeO Hf Ydi Hf eMeO Hf Ydi GdLYaQi GdaGQbi ai gPg GdMQha GdNjQ hGdNHQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs